2020
DOI: 10.1007/s13253-020-00385-4
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Development of Animal Density Estimation Using Random Encounter Modelling

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…All of the models mentioned above have had their accuracy tested using simulations, and in some cases with field data, but none has been demonstrated to consistently yield accurate estimates for a variety of species under field conditions. There has been ongoing development of the REM framework (Rowcliffe et al 2011, 2014, 2016, Lucas et al 2015, Gilbert et al 2020, Jourdain et al 2020), but practical applications have had mixed success due to inappropriate survey design or difficulties estimating the speed of animal movement (Rovero and Marshall 2009, Zero et al 2013, Anile et al 2014, Cusack et al 2015, Balestrieri 2016, Caravaggi et al 2016). Nakashima et al (2020) estimated densities and relationships between density and habitat covariates for sympatric duiker species and concluded that the method could be effective for estimating ungulate densities.…”
Section: Introductionmentioning
confidence: 99%
“…All of the models mentioned above have had their accuracy tested using simulations, and in some cases with field data, but none has been demonstrated to consistently yield accurate estimates for a variety of species under field conditions. There has been ongoing development of the REM framework (Rowcliffe et al 2011, 2014, 2016, Lucas et al 2015, Gilbert et al 2020, Jourdain et al 2020), but practical applications have had mixed success due to inappropriate survey design or difficulties estimating the speed of animal movement (Rovero and Marshall 2009, Zero et al 2013, Anile et al 2014, Cusack et al 2015, Balestrieri 2016, Caravaggi et al 2016). Nakashima et al (2020) estimated densities and relationships between density and habitat covariates for sympatric duiker species and concluded that the method could be effective for estimating ungulate densities.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple detectors are also necessary to appropriately characterize and quantify the variance in the data, and thus estimate the error in the density estimates. Error estimation in REM models is a non-trivial issue, given that (1) the estimator is a ratio with variable numerator and denominator (Jourdain et al 2020), (2) process error and observation error are nearly indistinguishable (Rowcliffe et al 2008), and (3) the underlying data-generating process is not always the same (e.g. Poisson vs. negative binomial distribution of the number of detections).…”
Section: Discussionmentioning
confidence: 99%
“…Rowcliffe et al (2008) recognized that maximum likelihood methods would be ideal to characterize variance but, given these difficulties, they and other researchers have instead relied on nonparametric bootstrapping (Manzo et al 2012;Cusack et al 2015;Caravaggi et al 2016). More recently, Jourdain et al (2020) proposed suitable alternatives to estimate variance using the delta method, which compounds different sources of variability. Our model shares some of the same sources of error and underlying movement process as the 2D case, so these variance estimation methods would also be applicable in the 3D case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations